Tiempo de juego Free Fire y Expresión de la Ira en Adolescentes De 12 a 16 Años en un Colegio Privado de la Ciudad de Bogotá (2022)
This work is carried out in order to determine if the time that adolescents use the Free Fire video game generates any alteration in the expression of anger, for this a group of adolescents between the ages of 12 and 16 was chosen. in a private Bilingual Del Bosque school in the city of Bogotá; To measure the Expression of anger, the STAXI-NA instrument was used, which is a scale that measures the expression of anger with the state of trait in children and adolescents, likewise the results that were obtained demonstrated that if there is a relationship between the variable of time and the expression of anger, which proves that the longer the game time, the subjects can generate changes in their behaviors